p62-Keap1-NRF2-ARE Pathway: A Contentious Player for Selective Targeting of Autophagy, Oxidative Stress and Mitochondrial Dysfunction in Prion Diseases - Shah, Syed Zahid Ali; Zhao, Deming; Hussain, Tariq; Sabir, Naveed; Mangi, Mazhar Hussain; Yang, Lifeng (Frontiers in Molecular Neuroscience, 2018)
Prion diseases are a group of fatal and debilitating neurodegenerative diseases affecting humans and animal species. The conversion of a non-pathogenic normal cellular protein (PrPc) into an abnormal infectious, protease-resistant, pathogenic form prion protein scrapie (PrPSc), is considered the etiology of these diseases. PrPSc accumulates in the affected individual’s brain in the form of extracellular plaques. The molecular pathways leading to neuronal cell death in prion diseases are still unclear. The free radical damage, oxidative stress and mitochondrial dysfunction play a key role in the pathogenesis of the various neurodegenerative disorders including prion diseases. The brain is very sensitive to changes in the redox status. It has been demonstrated that PrPc behaves as an antioxidant, while the neurotoxic prion peptide PrPSc increases hydrogen peroxide toxicity in the neuronal cultures leading to mitochondrial dysfunction and cell death. The nuclear factor erythroid 2-related factor 2 (NRF2) is an oxidative responsive pathway and a guardian of lifespan, which protect the cells from free radical stress-mediated cell death. The reduced glutathione, a major small molecule antioxidant present in all mammalian cells, and produced by several downstream target genes of NRF2, counterbalances the mitochondrial reactive oxygen species (ROS) production. In recent years, it has emerged that the ubiquitin-binding protein, p62-mediated induction of autophagy, is crucial for NRF2 activation and elimination of mitochondrial dysfunction and oxidative stress. The current review article, focuses on the role of NRF2 pathway in prion diseases to mitigate the disease progression.